2003
DOI: 10.1191/1358863x03vm471oa
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid treatment in patients with healed venous ulcer: flow cytometry analysis suggests increased CD11b expression on neutrophil granulocytes in the circulation

Abstract: The objective was to determine the activation of white blood cells (WBCs) and endothelial cells in patients with healed venous ulcer and the influence of the standing position and of treatment with flavonoids. Ten patients with a healed venous ulcer were treated with flavonoid substance (90% diosmin), 1000 mg three times daily for 30 days. Blood samples were taken from arm and dorsal foot veins before and after standing for 30 minutes. Blood sampling was performed before treatment, after three days, one month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Phytochemical studies of the methanol extract of Solanum torvum revealed the presence of flavonoids, sterols and triterpens which may be responsible for the anti-ulcer properties. Many compounds from these chemical classes such as nimbidine, ursolic acid, oleanolic acid, qualetin, diosmin, wogonin and sophoradine (Sasajima et al, 1978;Pillai and Santhakumari, 1984;Danielson et al, 2003;Kahraman et al, 2003;Park et al, 2004) have been shown to possess anti-ulcer properties. Moreover, the fraction F which was very rich in flavonoids and triterpens exhibited the most potent protective effect.…”
Section: Discussionmentioning
confidence: 98%
“…Phytochemical studies of the methanol extract of Solanum torvum revealed the presence of flavonoids, sterols and triterpens which may be responsible for the anti-ulcer properties. Many compounds from these chemical classes such as nimbidine, ursolic acid, oleanolic acid, qualetin, diosmin, wogonin and sophoradine (Sasajima et al, 1978;Pillai and Santhakumari, 1984;Danielson et al, 2003;Kahraman et al, 2003;Park et al, 2004) have been shown to possess anti-ulcer properties. Moreover, the fraction F which was very rich in flavonoids and triterpens exhibited the most potent protective effect.…”
Section: Discussionmentioning
confidence: 98%
“…The major limitation of this meta‐analysis is that it excludes studies that presented data as figures, medians, or geometric means . However, the exclusion of these studies did not affect the results considering that also these studies suggest that chronic ingestion of fruit , wine and tea reduces TNF‐α and IL‐6 , while results on soy intervention are more contrasting and none of these studies used quercetin as pure molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Using the search criteria, after exclusion of irrelevant references, a total of 110 intervention studies after flavonoids‐rich food and beverages consumption or pure molecules and food extracts administration were identified as suitable and were retrieved for complete review . Figure depicts the flow of studies in this review and the four‐phase diagram of meta‐analysis, according to the PRISMA Statement .…”
Section: Methodsmentioning
confidence: 99%
“…Of all the anti-inflammatory medications used to treat venous leg ulcers, flavonoid, a pigmented, polyphenolic compound naturally synthesized by plants, is the most extensively studied. It is postulated to act by protecting cells from damage caused by hypoxia, decreasing permeability and fragility of vein vales and venous walls, free radical formation, and affect expression of adhesion molecules in granulocytes such as neutrophils (Danielsson et al, 2003;Pascarella et al, 2005). Others have also found it to increase venous elasticity (Ibegbuna et al, 1997) and lymph drainage (Allegra et al, 1998).…”
Section: ''Fibrin Cuff'' Theorymentioning
confidence: 95%
“…Duplex ultrasound, the gold standard in diagnosing venous reflux, was used in only half of the studies. Finally, of the 18 observational or interventional studies, 15 did not exclude patients with diabetes (Burnand et al, 1982a, b;Coleridge Smith et al, 1988;Thomas et al, 1988;Cheatle et al, 1990;Trengove et al, 1996;Weyl et al, 1996;Loots et al, 1998;Takase et al, 1999;Danielsson et al, 2003) or infection (Burnand et al, 1982a, b;Coleridge Smith et al, 1988;Thomas et al, 1988;Layton et al, 1994;Trengove et al, 1996;Weyl et al, 1996;Loots et al, 1998;Takase et al, 1999;Abd-El-Aleem et al, 2005). Given the effects of diabetes and infection on chronic inflammation, it is difficult to clearly identify the role of inflammatory cells in chronic venous disease.…”
Section: Inflammatory Cell ''Trap'' Theorymentioning
confidence: 97%